2017
DOI: 10.1093/mmy/myx086
|View full text |Cite
|
Sign up to set email alerts
|

Tinea folliculorum complicating tinea of the glabrous skin: an important yet neglected entity

Abstract: Dermatophytes are capable of infecting the skin and its appendages such as nails and hairs producing a variety of clinical conditions. Hair invasion by dermatophytes is a key feature of tinea capitis and tinea barbae but not of tinea of glabrous skin. In this project, we studied the clinico-mycological aspects of follicular involvement in patients with dermatophytosis of the glabrous skin. In total, 16 patients, eight males and eight females, were included in the study. All were adults except for one girl. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…The dysbiosis may be associated with previous findings of fewer and atrophic sebaceous glands in HS and thereby a subsequent reduced sebum excretion rate in HS. 2 Taken together, these observations led us to speculate about the potential utility of probiotics in HS, which has also been described in other chronic inflammatory skin diseases. 3…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…The dysbiosis may be associated with previous findings of fewer and atrophic sebaceous glands in HS and thereby a subsequent reduced sebum excretion rate in HS. 2 Taken together, these observations led us to speculate about the potential utility of probiotics in HS, which has also been described in other chronic inflammatory skin diseases. 3…”
mentioning
confidence: 56%
“…1 It has been recently reported that the presence of curly and coiled hairs is a new and specific trichoscopic feature of fungal infection of the vellus hair. 2 Use of Wood lamp in a dark room can help identify Microsporum canis infection of the hair; however, this can be challenging because of the need for eye protection and the possible distressing effect of a dark room on small children.…”
mentioning
confidence: 99%
“…In the last 12 years, 63 cases have been reported in the English literature. 1,[4][5][6][7][8][9][10][11][12][13][14] People of all ages (0-64 years) can be affected by tinea of vellus hair. The face and neck (37%) and upper arms (33%) have been the most involved areas, followed by the lower extremities (14%), trunk (12%), and buttocks (4%).…”
Section: The Infection Of Vellus Hair Indicates Fungal Infection Invo...mentioning
confidence: 99%
“…The SEM observation in this case showed that spores were mainly concentrated in and around the hair follicle, severely damaging its structure, which is in accord with Sun's findings on the histopathology of tinea of vellus hair. 12 The involvement of the hair follicle may result in diseases such as Majocchi's granuloma, a rare granulomatous folliculitis caused by dermatophytes. 14 Forty-seven percent of patients used topical corticosteroids before presentation, 47% had topical antifungals, and 6% had oral antifungals.…”
Section: The Infection Of Vellus Hair Indicates Fungal Infection Invo...mentioning
confidence: 99%
See 1 more Smart Citation